Influence of Socioeconomic Factors on Transit Demand During the COVID-19 Pandemic: A Case Study of Bogotá’s BRT System - Caicedo, Juan D.; Walker, Joan L.; González, Marta C. (Frontiers in Built Environment, 2021)
The COVID-19 pandemic restricted most economic and social activities, impacting travel demand for all transportation modes and especially for transit. We hypothesize that the shifts in travel demand varied by socioeconomic status, and we assess the differential impact of COVID-19 in the Bus Rapid Transit (BRT) patronage across various socioeconomic groups in Bogotá. We built a database of frequent transit users with data collected by smartcards in Bogota's BRT system between January and October 2020. For each user in the database, we labelled their home and work stations. Transactions at other stations are classified as ``other." The stratum (a government socioeconomic classification of residential units in Colombia) of a BRT station's service area was assigned using an estimated probability vector for each user belonging to a specific stratum; this data is validated with aggregate strata distributions in the 2019 household travel survey. Our study found that the reduction in transactions for lower-strata users is significantly less than that of the middle and high strata. The magnitude of this difference varies over time but stabilizes after the end of the lockdown. The growth rate of ``other" transactions per thousand people is greater than the growth for home and work locations, especially for the lowest strata. Other studies have shown that the radius of gyration (Rg) (a measure of how far individuals travel away from home) has decreased about 50% after the lockdowns. Our study shows that when measuring Rg only for users that continued using BRT, the Rg slightly decreased for lower and medium strata but increased for high strata. The contribution of this study is to build a method to classify BRT transactions of frequent users by strata and to describe their trends to expand our understanding of the COVID-19 lockdowns impacts in the Global South context. These results are a starting point to inform policy and decision-makers to guide the recovery efforts to improve transit accessibility and level of service for captive users such as low-stratum users.